World development report 2004 making services work for poor people - Devarajan, Shantayanan 1954-.; Reinikka, Ritva; World Bank. ([Washington, D.C.] World Bank and Oxford University Press, 2004)
"The World Development Report (WDR) 2004 builds an analytical, and practical framework for using resources, whether internal or external, more effectively by making services work for poor people. The focus is on those services that have the most direct link with human development - education, health, water, sanitation, and electricity. This presents an enormous challenge, because making services work for the poor involves changing, not only service delivery arrangements, but also public sector institutions, and how foreign aid is transferred. This WDR explores the many dimensions of poverty, through outcomes of service delivery for poor people, and stipulates affordable access to services is low - especially for poor people - in addition to a wide range of failures in quality. The public responsibility is highlighted, addressing the need for more public spending, and technical adjustments, based on incentives and understanding what, and why services need to be improved. Thus, through an analytical framework, it is suggested the complexity of accountability must be established, as well as instruments for reforming institutions to improve services, illustrated through various case studies, both in developing, and developed countries. The report further outlines that scaling up reforms means sectoral reforms must be linked to ongoing, or nascent public sector reforms, in areas such as budget management, decentralization, and public administration reform, stimulated through information as a catalyst for change, and as an input to prod the success of other reforms." -- World Bank description.
Services can work for poor people but too often they fail -- Governments should make services work -- The framework for service provision -- Clients and providers -- Citizens and politicians -- Policymakers and providers -- Basic education services -- Health and nutrition services -- Drinking water, sanitation, and electricity -- Public sector underpinnings of service reform -- Donors and service reform.
"A Copublication of the World Bank and Oxford University Press"--T. p. and verso.
"This Report has been prepared by a team led by Shantayanan Devarajan and Ritva Reinikka ... [et al.] ..."--P. xiii.
"This Report has been prepared by a team led by Shantayanan Devarajan and Rivva Reinikka ..."--P. xiii.
Also available in print format.
Keywords: Rural poor -- Services for -- Developing countries; Social service, Rural -- Developing countries; Poverty -- Developing countries; Public welfare -- Developing countries